Gambit: An Interactive Database Design Tool for Data Structures, Integrity Constraints, and Transactions - Braegger, R.P.; Dudler, A.M.; Rebsamen, J.; Zehnder, C.A. (IEEE transactions on software engineering, 1985)
The design of a database is a rather complex and dynamic process that requires comprehensive knowledge and experience. There exist many manual design tools and techniques, but the step from a schema to an implementation is still a delicate subject. The interactive database design tool Gambit supports the whole process in an optimal way. It is based on an extended relational-entity relationship model. The designer is assisted in outlining and describing data structures and consistency preserving update transactions. The constraints are formulated using the database programming language Modula/R which is based upon first-order predicate calculus. The update transactions are generated automatically as Modula/R programs and include all defined integrity constraints. They are collected in so-called data modules that represent the only interface to the database apart from read operations. The prototype facility of Gambit allows the designer to test the design of the database. The results can be used as feedback leading to an improvement of the conceptual schema and the transactions.